2008
DOI: 10.1176/ps.2008.59.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Preferences for Seclusion or Forced Medication in Acute Psychiatric Emergency in the Netherlands

Abstract: Many patients on acute psychiatric wards have a clear preference between seclusion and medication. Patients appreciated receiving explanations of the reasons for the use of a restrictive measure and discussing their preferences with staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 8 publications
1
39
0
1
Order By: Relevance
“…Evidently, being ' calm' does not necessarily imply a sense of well-being, it can be a manifestation of immobilization or shutting down. If the use of seclusion can be perceived as punishment or even torture (Veltkamp et al, 2008) then people are likely to act as though they have calmed down in order to be let out.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, being ' calm' does not necessarily imply a sense of well-being, it can be a manifestation of immobilization or shutting down. If the use of seclusion can be perceived as punishment or even torture (Veltkamp et al, 2008) then people are likely to act as though they have calmed down in order to be let out.…”
Section: Discussionmentioning
confidence: 99%
“…Women were requesting PRNs on the wards and being offered them, before the need for restraint. Some research studies argue that the use of PRN as a proactive method is much more preferable to women than more coercive methods (for example, Veltkamp et al 2008). Ellie also said that she does not appreciate staff using humour in this situation.…”
Section: Alternatives To Restraintmentioning
confidence: 99%
“…A Dutch study reported gender to be associated with patients' preferences as to whether they want to be secluded or medicated when needed: Women preferred medication while men chose seclusion (Veltkamp et al 2008). On the whole, women more often prefer interpersonal interventions and seek help earlier (Seeman 2006).…”
Section: Coerced Patients' Perceptions Of Their Overall Treatmentmentioning
confidence: 99%